Proposal for an Entrepreneur Tool in the Design of a Business Model (GEON Journal (Management, Organizations and Business), 2020)
The evolution of the entrepreneurship has led to the development and application of different tools that allow the achievement of their goals. Currently, the entrepreneurs consider innovation and business models as two fundamental objectives of their structure, so they make use of methodologies that allow them to create strategies and value propositions that generate a positive impact on the acceptance of their products and services. Design thinking, Lean startup and Business model canvas represent three revolutionary instruments for the design and innovation of business and products. Its use has been popularized by large companies such as Apple or IDEO. The present investigation makes a documentary review about the three most used entrepreneurial tools in Mexico: Canvas, Design Thinking and Lean Startup; in order to analyze its application structure and propose an 11-step model that allows measuring the impact of solutions based on the design of a business model, in a more comprehensive way
Keywords: Bussines Model Canvas; Design Thinking; Lean Startup; Business Model